The Effectiveness of a Proposed Program Based on The Theory of Brain-Based Learning in Developing Scientific Sense Among Seventh Grade Students in Biology - Haso, Ashqi Suleman; Muhammad, Afrah Yassin (Zanco Journal of Human Sciences, 2024)
The current research aims at identifying the effectiveness of a proposed program based on brain-based learning strategies in developing scientific sense skills for seventh grade students in biology by applying the emotional side scale of scientific sense. To achieve the aim of the study, the researchers followed the experimental approach. Moreover, the tool consisted of (46) items to measure the skills of the emotional side of the scientific sense. The research sample consisted of (60) students who were randomly divided into two groups: an experimental group (30 students) and a control group (30 students). During this period, the experimental group was taught through the proposed program according to brain-based learning strategies while the control group using the usual method. The results of the study showed that the performance of the students in the experimental group was better than the control group who studied according to the usual method in testing the emotional side of the scientific sense in favor of the experimental group.